Perlindungan Data Anak, Regulasi, dan Solusi untuk Keamanan Media Digital Tiktok - Gusti Ayu Putu Vebyardani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of information technology in this modern era means that people increasingly need things in life, especially with the increasing prevalence of mobile phone technology and other smart phones which are widely distributed in society. This technology makes everything more efficient and easier. Protection of children's data on social media, especially on the social media platform TikTok, is an issue that is increasingly occurring in the digital modernization realm. With the rapid growth of children's users who are increasingly connected to various online platforms, although TikTok provides space for expression and creativity, on the one hand, TikTok also presents various risks related to the collection and misuse of children's personal data. The data collected on this platform, which will include information such as location, content data preferences, and social interactions, will ultimately be used for advertising purposes and can even be misused by irresponsible parties spread across the Tiktok platform. This article aims to explore aspects of protecting children's personal data on TikTok, as well as including the policies implemented by TikTok and the government.